2021
DOI: 10.3390/ijerph18052719
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: Integrase Strand Transfer Inhibitors Drug Resistance Mutations in Puerto Rico HIV-Positive Individuals

Abstract: The HIV-1 integrase viral protein is responsible for incorporating the viral DNA into the genomic DNA. The inhibition of viral integration into host cell DNA is part of recent therapeutic procedures. Combination therapy with protease and reverse transcriptase inhibitors has demonstrated good synergistic results in reducing viral replication. The purpose of this study is to assess the occurrence of integrase drug resistance mutations from the period comprising 2013 through 2018 in Puerto Rico (PR). We analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The United States Food and Drug Administration (United States FDA) has approved the following five drugs for clinical use: dolutegravir (DTG), raltegravir (RAL), elvitegravir (EVG), bictegravir (BIC), and cabotegravir (CAB). Despite integrase inhibitors plays an effective role in antiretroviral action with a novel mechanism of action, resistance is inevitable (Jiang et al, 2016), and previously published studies have shown that there were important INSTIs resistance mutations in newly diagnosed HIV-1 patients in Spain, Canada, and the United States (Stekler et al, 2015;Ji et al, 2018;Casadellà et al, 2020;López et al, 2021). Major INSTIs resistance mutations have also been discovered in Yunnan (Deng et al, 2019) and Jiangsu (Yin et al, 2021) in China, and INSTIs resistance mutations were found in our neighboring provinces such as Henan (Yang et al, 2021), Beijing (Yu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The United States Food and Drug Administration (United States FDA) has approved the following five drugs for clinical use: dolutegravir (DTG), raltegravir (RAL), elvitegravir (EVG), bictegravir (BIC), and cabotegravir (CAB). Despite integrase inhibitors plays an effective role in antiretroviral action with a novel mechanism of action, resistance is inevitable (Jiang et al, 2016), and previously published studies have shown that there were important INSTIs resistance mutations in newly diagnosed HIV-1 patients in Spain, Canada, and the United States (Stekler et al, 2015;Ji et al, 2018;Casadellà et al, 2020;López et al, 2021). Major INSTIs resistance mutations have also been discovered in Yunnan (Deng et al, 2019) and Jiangsu (Yin et al, 2021) in China, and INSTIs resistance mutations were found in our neighboring provinces such as Henan (Yang et al, 2021), Beijing (Yu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The United States Food and Drug Administration (United States FDA) has approved the following five drugs for clinical use: dolutegravir (DTG), raltegravir (RAL), elvitegravir (EVG), bictegravir (BIC), and cabotegravir (CAB). Despite integrase inhibitors plays an effective role in antiretroviral action with a novel mechanism of action, resistance is inevitable ( Jiang et al, 2016 ), and previously published studies have shown that there were important INSTIs resistance mutations in newly diagnosed HIV-1 patients in Spain, Canada, and the United States ( Stekler et al, 2015 ; Ji et al, 2018 ; Casadellà et al, 2020 ; López et al, 2021 ). Major INSTIs resistance mutations have also been discovered in Yunnan ( Deng et al, 2019 ) and Jiangsu ( Yin et al, 2021 ) in China, and INSTIs resistance mutations were found in our neighboring provinces such as Henan ( Yang et al, 2021 ), Beijing ( Yu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%